Design and analysis of E-glass gear box housing in tractor and optimization of its design parameters. (2022) - Mujiburrahman, K.; Saravanakumar, S.; Satheesh kumar, K.; Carciyo kaviya, J.J.; Krishnaraj, R.
Abstract: A significant part of an automobile is the gear box (tractor) casing. The primary objective of using the Gearbox casing is to embrace and allow the transmission of the Gearbox. The Gearbox is a mechanism that regulates speed or torque between the flywheel and the differential. The main shaft and lay shaft with gears equipped embraces the gear box. This paper deals with the modeling and study as an alternative material of the gear box casing for a tractor with E-Glass. Through the development of the simulation software platform ANSYS, it is analyzed statically with different design parameters such as web thickness, gear box housing depth and gear box housing thickness. In order to determine the stress produced and deformation degree, the gear box with traditional Grey cast iron is analyzed; it is then compared with the housing of the E-Glass Gear box. The outcome will be studied and evaluated after study, various combinations of design parameters were used to achieve the design that minimum output in failure at higher load s has better deformation characteristics. Finally, in order to design the gear box housing, an optimized design parameter is obtained.[1]